PENERAPAN STRATEGI REACTDALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN BILANGAN CACAH : Penelitian Tindakan Kelas Pada Siswa Kelas II SDN Cibeunying Kec. Cibodas Lembang Tahun Ajaran 2013/2014 - Setiowati, Nurul (2014)
Classroom Action Research was conducted in a class II SDN Cibeunying with students numbering 21 students consisted of 12 female students and as many as nine boys. The background of this study is the low numeracy skills of students on multiplication natural numbers caused by the teacher's teaching methods and strategies that apply more or conventional lecture method of teaching, the teacher was just having students memorize multiplication without give understanding the basic concept of multiplication, and teachers rarely use the media in the concrete to provide insight to students. The purpose of this study was to determine how the planning and implementation of learning mathematics with REACT strategy, as well as to describe the increase in students' numeracy multiplication after applying REACT strategy in learning mathematics. The method used in this study is the Class Action Research Model Kemmis and Taggart through two cycles. To obtain data to support this research, made learning instruments and data collection instruments. Data were analyzed by means of quantitative and qualitative. The results of this study are math lesson plan on multiplication with REACT strategy has been designed to systematically and according to curriculum set by the government, the implementation of learning was going well and there is an increasing arithmetic multiplication natural numbers significantly during the study. This can be seen in the rat and the average completeness increased student learning. In the first cycle, the average class II SDN Cibeunying of 68.9 and an increase in cycle II to 83.76. While the views of mastery learning in the first cycle is 66.7% increased to 95.2% in the second cycle. In addition, the gain index scores average grade of 0.60 with a moderate interpretation. It is expected that teachers can implement strategies that REACT in mathematics learning numeracy skills of students on multiplication natural numbers can be increased. And teachers also need to increase the professionalism and creativity by providing innovations in learning that can increase the quality of learning. Keywords: REACT Strategy, Learning Math, Arithmetic Capability, Multiplication Numbers Count an siswa berjumlah 21 orang siswa yang terdiri dari 12 orang siswa perempuan dan sebanyak sembilan orang siswa laki-laki. Latar belakang penelitian ini adalah rendahnya kemampuan berhitung siswa pada perkalian bilangan cacah yang diakibatkan oleh metode dan strategi mengajar guru yang lebih banyak menerapkan metode ceramah atau konvensional dalam mengajar, guru pun hanya menyuruh siswa untuk menghafal perkalian tanpa memberikan pemahaman konsep dasar dari perkalian, dan guru jarang menggunakan media yang kongkrit dalam memberikan pemahaman kepada siswa. Tujuan penelitian ini adalah untuk mengetahui bagaimana perencanaan pembelajaran matematika dengan Strategi REACTdanuntuk mendeskripsikan pelaksanaan serta peningkatan kemampuan berhitung perkalian siswa setelah menerapkan strategi REACT pada pembelajaran matematika. Metode penelitian yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas dengan Model Kemmis and Taggart melalui dua siklus. Untuk memperoleh data yang mendukung penelitian ini, dibuat instrumen pembelajaran dan instrumen pengumpul data. Data dianalisis dengan cara kuantitatif dan kualitatif. Hasil penelitian ini yaitu perencanaan pembelajaran matematika pada perkalian dengan Strategi REACT telah dirancang dengan sistematis dan sesuai dengan kurikulum yang ditetapkan oleh pemerintah, pelaksanaan pembelajaran pun berlangsung dengan baik dan terdapat peningkatan kemampuan berhitung perkalian bilangan cacah yang cukup signifikan selama penelitian. Hal tersebut dapat terlihat pada rat-rata dan ketuntasan belajar siswa yang mengalami peningkatan. Pada siklus I rata-rata kelas II SDN Cibeunying sebesar 68,9 dan mengalami peningkatan pada siklus II menjadi 83,76. Sedangkan dilihat dari ketuntasan belajar pada siklus I yaitu 66,7% meningkat menjadi 95,2% pada siklus II. Selain itu, indeks gain skor rata-rata kelas sebesar 0,60 dengan interpretasi sedang. Diharapkan guru dapat menerapkan Strategi REACT dalam pembelajaran matematika agar kemampuan berhitung siswa pada perkalian bilangan cacah dapat meningkat. Dan guru pun perlu meningkatkan profesionalitas dan kreativitas dengan memberikan inovasi dalam pembelajaran sehingga kualitas pembelajaran dapat meningkat. Kata kunci : Strategi REACT, Pembelajaran Matematika, Kemampuan Berhitung, Perkalian Bilangan Cacah